Application of the WHOQOL-BREF Scale for Evaluating Quality of Life Among Chronic Kidney Disease Patients: A Cross-Sectional Study - Patil, Harshavardhan; Salimath, Geetanjali; Karishetti, Mallikarjun; Wariman, Ifraa (International Journal of Pharmaceutical Investigation, 2026)
Background Chronic Kidney Disease (CKD) significantly impacts QOL through physical, Psychological, and social challenges. This study explores the use of WHOQOL-BREF to assess QOL in dialysis and non-dialysis patients across four domains-Physical, Psychological, Social, and Environmental well-being-along with overall health. It also examines the effects of sociodemographic and disease-related factors on QOL, providing insights into the challenges faced by CKD patients. Purpose This study aims to assess the Quality of Life (QOL) across various domains using the WHOQOL-BREF and to compare the QOL of Chronic Kidney Disease (CKD) patients undergoing dialysis with those who are not. Materials and Methods A cross-sectional observational study was conducted at KLE’s Dr. Prabhakar Kore Charitable Hospital and Medical Research Centre, Belagavi. A total of 106 CKD patients aged 18 and above were included. Data were collected through structured interviews using the WHOQOL-BREF questionnaire, which assesses QOL on a scale of 0-100. Statistical analysis was performed using SPSS v29, with Pearson’s correlation used to evaluate relationships between QOL and various factors. Results The study found that dialysis patients had lower QOL scores across all domains than non-dialysis patients. Physical limitations, fatigue, and Psychological distress were prevalent among those undergoing dialysis. Additionally, CKD stage progression was strongly associated with declining QOL. Factors such as education, socioeconomic status, and social support positively influenced QOL, while comorbidities and prolonged dialysis duration negatively impacted well-being. Conclusion This study highlights the need for comprehensive CKD management, integrating medical treatment with Psychological and social support. Addressing comorbidities, enhancing mental health care, and improving healthcare accessibility can significantly improve the QOL of CKD patients. Further research is required to develop long-term strategies for QOL enhancement in CKD populations.
Keywords: QOL (Quality of Life); CKD (Chronic Kidney Disease); ESRD (End-Stage Kidney Disease); (MHD) Maintenance Haemodialysis